On The Surface of The Skin - Nur Aifiah Binti Ibrahim (Britain International for Academic Research (BIAR) Publisher, 2026)
The dermatologists have recommended the usage of more melanin and skin-friendly products. The tyrosines seem to be unbearably unbeaten for the whole process of closing the end products. The protein dietary pattern that helps to energise and promote massive transpiration in the vegetables state. The different vitamins and other oxidized materials for the awakening of senses to held at a fast pace of recovery. The controllable oil glands and sweating pores are for the best in both worlds. Mycobacterium and the skin organ that requires antibiotics as the perfect combination for healthy antibodies and perfect skincare.